Sensory Overresponsivity, Loneliness, and Anxiety in Taiwanese Adults with Autism Spectrum Disorder - Ya-Cing Syu; Ling-Yi Lin (Occupational Therapy International)
Purpose. Sensory overresponsiveness is highly prevalent in individuals with autism spectrum disorders (ASD) and typically persist into adulthood. However, the role of sensory processing difficulties in influencing emotional well-being among adults with ASD remains unclear. Additionally, the associations between sensory overresponsiveness, anxiety, and loneliness are yet to be examined among adults with ASD. Therefore, to address these critical gaps in the literature, we aimed to investigate the relationships among sensory avoiding, anxiety, and loneliness in a sample of adults with ASD. Participants. Seventy adults (age, 20–39 years) completed three self-reported measures. All participants had a documented diagnosis of ASD and had normal IQ. Methods. Sensory processing, loneliness, and anxiety were assessed with the Adult Sensory Profile, short-form UCLA loneliness scale, and Beck Anxiety Inventory, respectively. Results. Autism spectrum traits and sensory avoiding were associated with anxiety and loneliness. Participants who experienced sensory avoiding more frequently reported higher anxiety and feelings of loneliness, with loneliness mediating the relationship between sensory avoiding and anxiety. More anxiety symptoms in participants with greater sensory avoiding were associated with their higher level of loneliness. Conclusion. This study demonstrates that the relationships existed between sensory processing difficulties, loneliness, and anxiety among adults with ASD. Interventions regarding sensory processing difficulties and emotional well-being are substantial need for adults with ASD, and our results highlight the importance of sensory overresponsiveness and anxiety in evaluating and improving the psychological well-being of adults with ASD.